Low-cost carrier entry at small European airports: Low-cost carrier effects on network connectivity and self-transfer potential - Zeigler, Patrick; Pagliari, Romano; Suau-Sanchez, Pere; Malighetti, Paolo; Redondi, Renato (Elsevier, 2017)
Airport connectivity can improve the competitiveness of regions by attracting tourism and inward investment. Regions traditionally accessed international destinations via connecting flights to national gateway airports usually operated by full service network carriers (FSNC). However, the entry of low-cost carriers (LCC) in these markets has led to changes in incumbent FSNC service provision. We analyse how intra-European connectivity has changed at small airports between 2002 and 2012 and how LCC entry has affected the quality of day-return schedules in these markets. Results show that offline LCC connectivity is greater than that scheduled by FSNCs. Furthermore, LCC entry had a negative effect on the quality of the connectivity offered by FSNCs. Interestingly, we also found that day-return itineraries become more difficult for passengers in markets where the LCC is the sole operator. Regional policy-makers may need to more carefully consider the connectivity implications in the design of LCC start-up incentive schemes.